X-ray outbursts of ESO 243-49 HLX-1: Comparison with galactic low-mass X-ray binary transients - Yan, Z.; Zhang, W.; Soria, Roberto; Altamirano, D.; Yu, W. (2015)
We studied the outburst properties of the hyper-luminous X-ray source ESO 243-49 HLX-1, using the full set of Swift monitoring observations. We quantified the increase in the waiting time, recurrence time, and e-folding rise timescale along the outburst sequence, and the corresponding decrease in outburst duration, total radiated energy, and e-folding decay timescale, which confirms previous findings. HLX-1 spends less and less time in outburst and more and more time in quiescence, but its peak luminosity remains approximately constant. We compared the HLX-1 outburst properties with those of bright Galactic low-mass X-ray binary transients (LMXBTs). Our spectral analysis strengthens the similarity between state transitions in HLX-1 and those in Galactic LMXBTs. We also found that HLX-1 follows the nearly linear correlations between the hard-to-soft state transition luminosity and the peak luminosity, and between the rate of change of X-ray luminosity during the rise phase and the peak luminosity, which indicates that the occurrence of the hard-to-soft state transition of HLX-1 is similar to those of Galactic LMXBTs during outbursts. We found that HLX-1 does not follow the correlations between total radiated energy and peak luminosity, and between total radiated energy and e-folding rise/decay timescales we had previously identified in Galactic LMXBTs. HLX-1 would follow those correlations if the distance were several hundreds of kiloparsecs. However, invoking a much closer distance for HLX-1 is not a viable solution to this problem, as it introduces other, more serious inconsistencies with the observations.